Chega de samba: estratégias de recriação da identidade pelas brasileiras em pequim - Porto, Ana Carolina Costa (2014)
Discussions about the migration of Brazilians to several countries in America and Europe are frequent, however, few researches have dealt with the migration of Brazilians to China. For this reason, this thesis aims to analyze the migration history of fifteen Brazilian women living in Beijing and use it to represent the processes of several Brazilian women who have migrated to the People's Republic of China. At first, the goal of this research was to study the Brazilian community as a whole, but women have a much more significant role in building Brazilian identity since they run the main organization that congregates Brazilians in Beijing (Brapeq); women also organize events such as Beijing's Brazil Film Festival, Doc Brazil Festival and Brazil-China Book Club. Thus, we have carried out narrative interviews with fifteen women of different ages, social classes and lifestyles, who had different migration histories. The interviews, done at cafes, restaurants, the street, or the interviewee's home, aimed to trace these women's background in order to comprehend how each migration history contributes to building a different Brazilian identity. Based on these women's accounts, we intended to study the ways Brazilians socialize and associate, to understand Brapeq's role in integrating these people and disseminating Brazilian culture, as well as to analyze how Brazilian identity is built and rebuilt through the social fabric of Brazilians who have migrated.